Evaluation of different types of feline blood groups in cats of Isfahan, Iran - SALEHI-NAJAFABADI, E; KARIMI-DEHKORDI, M; JAFARIAN-DEHKORDI, M (Journal of the Hellenic Veterinary Medical Society, 2022)
There is a high demand for pet veterinary care due to the increasing tendency to keep pets in Iranian households. These include blood transfusions because incompatible blood groups can lead to some negative effects such as isoerythrolysis in cats. This study was the first attempt to evaluate the distribution of blood type of cats in Iran. Blood samples were collected from 63 domestic short hair cats in Isfahan, Iran and blood groups were determined by the kit card agglutination method (Rapid Vet-H IC Feline kits, Agrolabo, Scarmagno, Italy). According to the results, the frequency of blood types of A, B, and AB were 96.8%, 3.2%, and 0%, respectively. Card agglutination method is a fast method with high validity. Therefore, it is recommended for determining blood types in donor and recipient in veterinary hospitals and breeding centers.